Demolished and Displaced: Legal Protection for Flat Owners in Uninhabitable Buildings, West Jakarta - Windiahsari, Windiahsari; Putri, Eva Cornelia; Dharmaputra, Zean Nicholas (Universitas Negeri Semarang, 2025)
The rise in the construction of apartment buildings as a solution to limited land and housing needs in urban areas is not accompanied by comprehensive legal regulations, particularly regarding demolition and unit owner rights. In this context, demolition is part of an effort to improve building quality, but it often creates legal uncertainty and losses for unit owners, especially if the building is demolished due to aging without clear compensation. This research uses a normative method with a regulatory and legal theory approach to analyze developer responsibilities, apartment owner rights, and ideal forms of legal protection. The study results indicate a regulatory gap regarding compensation and protection for unit owners after demolition. Therefore, strengthening the legal system is necessary to guarantee comprehensive protection, including technical regulations for demolition, provision of temporary housing, and fair and proportional compensation mechanisms.